The approximation problems of solutions of the compressible fluid flow in an exterior domain - Leonavičienė, Teresė (Lietuvos matematikos rinkinys, 2002)
The approximation of solutions of the three-dimensional steady compressible flow (linearized problem) in an exterior domain is studied. The formal error estimates are obtained.